Film and method for manufacturing semiconductor package
By using a film with an elongation between 90% and 255% in the semiconductor package manufacturing process, the problem of peeling off the mold release layer and the antistatic layer is solved, and effective protection of the semiconductor package and reliability of the manufacturing process is achieved.
Patent Information
- Application Number
- CN202380060830.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-01
- Filing Date
- 2023-08-29
- Publication Date
- 2025-04-01
AI Technical Summary
In the process of manufacturing semiconductor packages using films, the increase in complex shapes and height differences leads to easy peeling of the release layer and the antistatic layer, causing damage to the semiconductor package.
A film is provided that includes a substrate, an antistatic layer and a release layer, and the elongation is determined under certain conditions by tensile tests to ensure an elongation between 90% and 255% to enhance the adhesion between layers.
The antistatic layer and the release layer of the film are not easy to peel off, effectively preventing damage to the semiconductor package during the release process, and improving the reliability of the manufacturing process.
Smart Images

Figure CN119744438A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to methods of manufacturing films and semiconductor packages.
[0002] This application claims priority from Japanese Patent Application No. 2022-139307 filed in Japan on September 1, 2022, and incorporates the contents of this application into this document. Background Art
[0003] The semiconductor element is sealed in the form of a package and mounted on a substrate to block and protect it from external gases. In the sealing of the semiconductor element, a curable resin such as epoxy resin is used. Resin sealing is performed by arranging the semiconductor element at a specified position in the mold, filling the mold with a curable resin and curing it. As a sealing method, transfer molding and compression molding are generally known. In the sealing of the semiconductor element, in order to improve the demoulding property of the package from the mold, a demoulding film is mostly arranged on the inner surface of the mold.
[0004] When a release film is used in manufacturing a semiconductor package, when the sealed semiconductor package is peeled off from the film, static electricity may be generated and the film may be charged, and the semiconductor package may be damaged due to discharge of the charged film.
[0005] In order to prevent the film from being charged, Patent Document 1 proposes providing an antistatic layer between the substrate and the release layer.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2016 / 125796 Summary of the invention
[0009] Technical problem to be solved by the invention
[0010] As the shapes of semiconductor packages have become more complicated in recent years, and the height difference of semiconductor packages with exposed parts has increased, the use of films to follow complex shapes has become more and more common. The inventors have found that when the film described in Patent Document 1 is used to follow complex shapes, the release layer and the antistatic layer are easily peeled off. If the release layer and the antistatic layer are peeled off, when the sealed semiconductor package is peeled off from the film, the release layer tends to adhere to the semiconductor package and remain.
[0011] The present invention provides a film in which a release layer and an antistatic layer are not easily peeled off, and a method for manufacturing a semiconductor package using the film.
[0012] Technical solutions adopted to solve technical problems
[0013] The present disclosure provides a film having the following structures [1] to
[15] and a method for manufacturing a semiconductor package.
[0014] [1] A film comprising a substrate, an antistatic layer provided on one surface of the substrate, and a release layer provided on the surface of the antistatic layer opposite to the substrate, wherein the film has an elongation greater than 90% and less than 255% as measured by a tensile test at 25°C and a speed of 100 mm / min and determined using the following formula.
[0015] Elongation (%) = (elongation at break (mm)) × 100 / (distance between clamps before stretching (mm))
[0016] [2] The film according to [1] above, wherein the substrate comprises at least one selected from fluororesins, polymethylpentene, syndiotactic polystyrene, polycyclic olefins, silicone rubber, polyester elastomers, polybutylene terephthalate, polyethylene terephthalate, and polyamide.
[0017] [3] The film according to [2] above, wherein the fluororesin comprises at least one selected from the group consisting of ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer and tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer.
[0018] [4] The film according to any one of [1] to [3] above, wherein the release layer comprises a reaction-cured product of a hydroxyl-containing (meth)acrylic polymer and a bifunctional or higher-functional isocyanate compound.
[0019] [5] The film according to [4] above, wherein the ratio of the isocyanate group of the isocyanate compound is 20 to 115 mol % relative to 100 mol % of the hydroxyl group of the hydroxyl-containing (meth)acrylic polymer.
[0020] [6] The film described in any one of [1] to [5] above, wherein the antistatic layer comprises a reaction-cured product of a carboxyl-containing (meth)acrylic polymer and at least one selected from a difunctional or higher aziridine compound and a difunctional or higher epoxy compound.
[0021] [7] The film according to [6] above, wherein the total ratio of the aziridine group of the aziridine compound and the epoxy group of the epoxy compound is 15 to 130 mol% relative to 100 mol% of the carboxyl group of the carboxyl-containing (meth)acrylic polymer.
[0022] [8] The film according to any one of [1] to [7] above, wherein the thickness of the substrate is 25 to 250 μm.
[0023] [9] The release film according to any one of [1] to [8] above, wherein the release layer has a thickness of 0.05 to 3 μm.
[0024]
[10] The film according to any one of [1] to [9] above, which is a release film used in a step of sealing a semiconductor element with a curable resin.
[0025]
[11] A method for manufacturing a semiconductor package, comprising: placing the film described in any one of [1] to
[10] on the inner surface of a mold; placing a substrate having a semiconductor element fixed thereto in the mold having the film placed thereon; sealing the semiconductor element in the mold with a curable resin to produce a sealed body; and demolding the sealed body from the mold.
[0026] Effects of the Invention
[0027] According to the present disclosure, it is possible to provide a film in which a release layer and an antistatic layer are not easily peeled off, and a method for manufacturing a semiconductor package using the film. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a schematic cross-sectional view showing one embodiment of the film of the present disclosure. DETAILED DESCRIPTION
[0029] Hereinafter, the embodiments of the present disclosure are described in detail. However, the embodiments of the present disclosure are not limited to the following embodiments. In the following embodiments, the constituent elements (including element steps, etc.) are not necessarily required unless otherwise specifically stated. The numerical values and their ranges are also not limited to the embodiments of the present disclosure.
[0030] In the present disclosure, the term "process" includes a process that is independent of other processes, and also includes a process if the purpose of the process can be achieved without being clearly distinguished from other processes.
[0031] In the present disclosure, a numerical range expressed by "to" includes the numerical values described before and after "to" as a minimum value and a maximum value, respectively.
[0032] In the numerical ranges recorded in the present disclosure, the upper limit or lower limit recorded in one numerical range can be replaced by the upper limit or lower limit of the numerical range recorded in other classifications. In addition, in the numerical ranges recorded in the present disclosure, the upper limit or lower limit of the numerical range can also be replaced by the value shown in the embodiments.
[0033] In the present disclosure, each component may include a plurality of corresponding substances. When a plurality of substances corresponding to each component are present in the composition, the content rate or content of each component refers to the total content rate or total amount of the plurality of substances present in the composition, unless otherwise specified.
[0034] When the embodiments are described with reference to the drawings in the present disclosure, the configuration of the embodiments is not limited to the configuration shown in the drawings. In addition, the dimensions of the components in the drawings are schematic, and the relative relationship between the dimensions of the components is not limited thereto.
[0035] In the present disclosure, the "unit" of a polymer refers to a part derived from a monomer that exists in a polymer and constitutes the polymer. In addition, a structure obtained by chemically converting the structure of a certain unit into a polymer is also referred to as a unit. In addition, depending on the circumstances, the unit derived from each monomer is described by the name of the monomer plus the name of the "unit".
[0036] In the present disclosure, films and sheets are collectively referred to as "films" regardless of their thickness.
[0037] In the present disclosure, acrylate and methacrylate are collectively referred to as “(meth)acrylate”, and acrylic acid and methacrylic acid are collectively referred to as “(meth)acrylic acid”.
[0038] In the present disclosure, a (meth)acrylic polymer is a polymer containing a unit based on a monomer having a (meth)acryloyl group or (meth)acrylic acid. Hereinafter, a monomer having a (meth)acryloyl group or (meth)acrylic acid is also referred to as a "(meth)acrylic monomer".
[0039] 〔membrane〕
[0040] The film of one embodiment of the present disclosure (hereinafter also referred to as "the present film") comprises a substrate, an antistatic layer provided on one surface of the substrate, and a release layer provided on the surface of the antistatic layer opposite to the substrate, wherein the elongation of the present film measured by a tensile test at 23°C and a speed of 100 mm / min and obtained by the following formula is greater than 90% and less than 255%. The elongation of the present film is preferably greater than 125% and less than 255%, more preferably greater than 175% and less than 255%, and particularly preferably greater than 225% and less than 255%.
[0041] Elongation (%) = (elongation at break (mm)) × 100 / (distance between clamps before stretching (mm))
[0042] "Tensile test" can be carried out by the method described in <Elongation> in the examples. Specifically, the film is cut into strips (50 mm wide and 100 mm long). The film is clamped and fixed in the fixture of a tensile testing machine (for example, RTC-131-A manufactured by Olyentec Co., Ltd.). The film is stretched at a speed of 100 mm / min with a distance of 10 mm between the fixtures before stretching until the film breaks, and the elongation (mm) at break is measured. The measurement is carried out at 23 ° C.
[0043] The inventors have found that when the film is used to manufacture a semiconductor package having a particularly complex shape, the antistatic layer and the release layer are not easily peeled off.
[0044] If the elongation is greater than 90%, it is considered that when a coating liquid for a release layer is applied on the antistatic layer to form the release layer, the antistatic layer is slightly dissolved by the solvent in the coating liquid, the surface of the antistatic layer becomes rough and the release layer penetrates therein, thereby improving the adhesion between the antistatic layer and the release layer.
[0045] Furthermore, if the elongation is less than 255%, it is considered that the release layer and the antistatic layer each have sufficient cohesive force, and cohesive failure in each layer can be suppressed when the film and the semiconductor package are peeled off.
[0046] The present film may have only a substrate, an antistatic layer, and a release layer, and other components are not particularly limited.
[0047] Figure 1 This is a schematic cross-sectional view showing one embodiment of the present film. Figure 1 The film 1 shown in the figure has a substrate 2, an antistatic layer 3 and a release layer 4 in this order. When the film 1 is used to seal a semiconductor element, the substrate 2 is arranged in contact with a mold, and after resin sealing, the release layer 4 is in contact with a sealing body (i.e., a semiconductor package after the semiconductor element is sealed). In addition to the substrate 2, the antistatic layer 3 and the release layer 4, the film 1 may also have other layers.
[0048] The components of the present film are described in detail below.
[0049] (Base material)
[0050] The material of the substrate is not particularly limited.
[0051] The substrate generally contains a resin, and examples of the resin include fluororesins, polymethylpentene, syndiotactic polystyrene, polycyclic olefins, silicone rubbers, polyester elastomers, polybutylene terephthalate, polyethylene terephthalate, and polyamide.
[0052] In one embodiment, from the viewpoint of excellent demoulding property of the film, the substrate preferably comprises a resin with demoulding property (hereinafter also referred to as "demolding resin"). Demolding resin refers to a resin having demoulding property in a layer composed of the resin. As demoulding resin, fluororesin, polymethylpentene, syndiotactic polystyrene, polycyclic olefin, silicone rubber, polyester elastomer, polybutylene terephthalate and polyamide etc. can be cited. From the viewpoint of excellent demoulding property, heat resistance, strength and elongation at high temperature, fluororesin, polymethylpentene, syndiotactic polystyrene and polycyclic olefin are preferred, and from the viewpoint of excellent demoulding property, fluororesin is more preferred.
[0053] The resin contained in the substrate may be one or more than one. The substrate is particularly preferably composed of only fluororesin alone. However, even when the substrate is composed of only fluororesin alone, it is not excluded that the substrate contains resins other than fluororesin within the scope of not damaging the effect of the invention.
[0054] As the fluororesin, a fluoroolefin polymer is preferred from the viewpoint of excellent mold release properties and heat resistance. A fluoroolefin polymer is a polymer having a unit based on a fluoroolefin. A fluoroolefin polymer may also have other units other than the unit based on a fluoroolefin.
[0055] Examples of the fluoroolefin include tetrafluoroethylene (hereinafter referred to as "TFE"), vinyl fluoride, vinylidene fluoride, trifluoroethylene, hexafluoropropylene (hereinafter referred to as "HFP"), and chlorotrifluoroethylene. The fluoroolefin may be used alone or in combination of two or more.
[0056] As the fluoroolefin polymer, ethylene-TFE copolymer (hereinafter also referred to as "ETFE"), TFE-HFP copolymer (hereinafter also referred to as "FEP"), TFE-perfluoro (alkyl vinyl ether) copolymer and TFE-HFP-vinylidene fluoride copolymer etc. can be cited. From the viewpoint of mechanical properties, it is preferably selected from at least one of ETFE and FEP. Fluoroolefin polymer can be used alone or in combination of two or more.
[0057] As the fluoroolefin polymer, ETFE is preferred from the viewpoint of high elongation at high temperature. ETFE is a copolymer having a unit derived from TFE (hereinafter also referred to as a "TFE" unit) and a unit derived from ethylene (hereinafter also referred to as an "E unit").
[0058] As ETFE, a polymer having TFE units, E units, and units based on a third monomer other than TFE and ethylene is preferred. The crystallinity of ETFE can be easily adjusted by the type and content of the units based on the third monomer, thereby easily adjusting the storage modulus or other tensile properties of the substrate. For example, ETFE has a tendency to improve tensile strength and elongation at high temperatures (especially around 180° C.) by having units based on a third monomer (especially a monomer having a fluorine atom).
[0059] The third monomer may, for example, be a monomer containing a fluorine atom or a monomer not containing a fluorine atom.
[0060] As the fluorine atom-containing monomer, the following monomers a1 to a5 may be mentioned.
[0061] Monomer a1: Fluorinated olefins having 2 or 3 carbon atoms.
[0062] Monomer a2: X(CF2) nFluorinated alkylethylenes represented by CY=CH2 (wherein X and Y are each independently a hydrogen atom or a fluorine atom, and n is an integer of 2 to 8).
[0063] Monomer a3: fluorovinyl ethers.
[0064] Monomer a4: fluorovinyl ethers containing functional groups.
[0065] Monomer a5: a fluorine-containing monomer having an aliphatic ring structure.
[0066] Specific examples of the monomer a1 include fluoroethylenes (eg, trifluoroethylene, vinylidene fluoride, vinyl fluoride, chlorotrifluoroethylene, etc.) and fluoropropylenes (eg, hexafluoropropylene (HFP), 2-hydropentafluoropropylene, etc.).
[0067] As the monomer a2, a monomer in which n is 2 to 6 is preferred, and a monomer in which n is 2 to 4 is more preferred. In addition, a monomer in which X is a fluorine atom and Y is a hydrogen atom, that is, a (perfluoroalkyl)ethylene is preferred.
[0068] Specific examples of the monomer a2 include the following compounds.
[0069] CF3CF2CH=CH2,
[0070] CF3CF2CF2CF2CH=CH2((perfluorobutyl)ethylene (hereinafter also referred to as "PFBE")),
[0071] CF3CF2CF2CF2CF=CH2、
[0072] CF2HCF2CF2CF=CH2,
[0073] CF2HCF2CF2CF2CF=CH2.
[0074] Specific examples of the monomer a3 include the following compounds. Among the following compounds, the monomer which is a diene is a cyclopolymerizable monomer.
[0075] CF2=CFOCF3,
[0076] CF2=CFOCF2CF3、
[0077] CF2=CF(CF2)2CF3(perfluoro(propyl vinyl ether) (hereinafter also referred to as "PPVE")),
[0078] CF2=CFOCF2CF(CF3)O(CF2)2CF3,
[0079] CF2=CFO(CF2)3O(CF2)2CF3、
[0080] CF2=CFO(CF2CF(CF3)O)2(CF2)2CF3,
[0081] CF2=CFOCF2CF(CF3)O(CF2)2CF3,
[0082] CF2=CFOCF2CF=CF2,
[0083] CF2=CFO(CF2)2CF=CF2.
[0084] Specific examples of the monomer a4 include the following compounds.
[0085] CF2=CFO(CF2)3CO2CH3、
[0086] CF2=CFOCF2CF(CF3)O(CF2)3CO2CH3,
[0087] CF2=CFOCF2CF(CF3)O(CF2)2SO2F.
[0088] Specific examples of the monomer a5 include perfluoro(2,2-dimethyl-1,3-dioxole), 2,2,4-trifluoro-5-trifluoromethoxy-1,3-dioxole, and perfluoro(2-methylene-4-methyl-1,3-dioxolane).
[0089] As the monomer not containing a fluorine atom, the following monomers b1 to b4 may be mentioned.
[0090] Monomer b1: olefins.
[0091] Monomer b2: vinyl esters.
[0092] Monomer b3: vinyl ethers.
[0093] Monomer b4: unsaturated acid anhydride.
[0094] Specific examples of the monomer b1 include propylene and isobutylene.
[0095] As a specific example of the monomer b2, vinyl acetate may be mentioned.
[0096] Specific examples of the monomer b3 include ethyl vinyl ether, butyl vinyl ether, cyclohexyl vinyl ether and hydroxybutyl vinyl ether.
[0097] Specific examples of the monomer b4 include maleic anhydride, itaconic anhydride, citraconic anhydride and 5-norbornene-2,3-dicarboxylic anhydride.
[0098] The third monomer may be used alone or in combination of two or more.
[0099] As the third monomer, monomer a2, HFP, PPVE and vinyl acetate are preferred from the viewpoint of easy adjustment of crystallinity and excellent tensile strength and elongation at high temperature (particularly around 180° C.), HFP, PPVE, CF3CF2CH=CH2 and PFBE are more preferred, and PFBE is particularly preferred. That is, as ETFE, a copolymer having a TFE unit, an E unit and a unit based on PFBE (hereinafter also referred to as a “PFBE unit”) is particularly preferred.
[0100] In ETFE, the molar ratio of TFE unit to E unit (TFE unit / E unit) is preferably 80 / 20 to 40 / 60, more preferably 70 / 30 to 45 / 55, and further preferably 65 / 35 to 50 / 50. When TFE unit / E unit is within the above range, ETFE has excellent heat resistance and mechanical strength.
[0101] The ratio of the units based on the third monomer in ETFE to the total of all units constituting ETFE (100 mol%) is preferably 0.01 to 20 mol%, more preferably 0.10 to 15 mol%, and further preferably 0.20 to 10 mol%. If the ratio of the units based on the third monomer is within the above range, ETFE has excellent heat resistance and mechanical strength.
[0102] When the units based on the third monomer include PFBE units, the ratio of the PFBE units to the total of all units constituting ETFE (100 mol%) is preferably 0.5 to 4.0 mol%, more preferably 0.7 to 3.6 mol%, and further preferably 1.0 to 3.6 mol%. When the ratio of the PFBE units is within the above range, the tensile strength and elongation of the film at high temperatures, particularly at about 180° C., are improved.
[0103] The substrate may be formed only of resin or may contain other components in addition to the resin. Other components include lubricants, antioxidants, antistatic agents, plasticizers, and mold release agents. From the perspective of not easily contaminating the mold, the substrate preferably does not contain other components.
[0104] The thickness of the substrate is preferably 25 to 250 μm, more preferably 50 to 150 μm, and further preferably 75 to 125 μm. If the thickness of the substrate is below the upper limit of the above range, the film can be easily deformed and has excellent mold compliance. If the thickness of the substrate is above the lower limit of the above range, the film is easy to handle, such as easy to handle in a roll-to-roll manner, and wrinkles are not easily generated when the film is stretched while covering the cavity of the mold.
[0105] The thickness of the substrate was measured in accordance with ISO 4591:1992 (B1 method of JIS K7130:1999: a method for measuring the thickness of a sample collected from a plastic film or plastic sheet by a mass method). The thickness of each layer of the film was measured in the same manner.
[0106] The surface of the substrate may have a surface roughness. The arithmetic mean roughness Ra of the surface of the substrate is preferably 0.2 to 3.0 μm, more preferably 0.5 to 2.5 μm. If the arithmetic mean roughness Ra of the surface of the substrate is above the lower limit of the above range, the demolding property from the mold is better. If the arithmetic mean roughness Ra of the surface of the substrate is below the upper limit of the above range, the film is not easy to form perforations.
[0107] The arithmetic mean roughness Ra is measured in accordance with JIS B 0601: 2013 (ISO 4287: 1997, Amd. 1: 2009). The reference length lr (cutoff value λc) for the roughness curve is set to 0.8 mm.
[0108] The substrate may be unstretched or stretched. For example, unstretched polyamide film, biaxially stretched polyamide film, biaxially stretched PET (polyethylene terephthalate) film, biaxially stretched PEN (polyethylene terephthalate) film, biaxially stretched syndiotactic polystyrene film and unstretched PBT (polybutylene terephthalate) film are commercially available. In addition, polyimide film, polyphenylene sulfide resin film and cross-linked polyethylene film etc. can also be used.
[0109] Any surface treatment can be implemented to the surface adjacent to other layers of the substrate. As surface treatment, corona treatment, plasma treatment, silane coupling agent coating and adhesive coating etc. can be exemplified. From the viewpoint of the adhesion between the substrate and other layers, preferably corona treatment or plasma treatment.
[0110] From the viewpoint of adhesion between the substrate and the adjacent layer, the wetting tension of the antistatic layer side surface of the substrate is preferably above 20 mN / m, more preferably above 30 mN / m, and particularly preferably above 35 mN / m. The upper limit of the wetting tension is not particularly limited and may be below 80 mN / m.
[0111] The substrate may be a single layer or a multilayer structure. As a multilayer structure, a structure in which a plurality of layers containing resins are stacked can be exemplified. In this case, the resins contained in each of the plurality of layers may be the same or different. From the viewpoints of mold compliance, tensile elongation, and manufacturing cost, the substrate is preferably a single layer. From the viewpoint of film strength, the substrate preferably has a multilayer structure.
[0112] Multilayer structure can be, for example, a structure obtained by laminating the above-mentioned layer containing release resin (preferably fluororesin) with a resin film (can be a film containing only resin) containing resins such as polyester, polybutylene terephthalate, polystyrene (preferably syndiotactic) or polycarbonate, or a structure obtained by laminating the layer containing the first release resin, the above-mentioned resin film and the layer containing the second release resin in sequence. The layer containing release resin and the resin film can also be laminated by an adhesive. Corona treatment or plasma treatment can be implemented to the single or both sides of each layer containing release resin. When substrate has the multilayer structure, the layer containing release resin is preferably configured on the antistatic layer side. When substrate has the multilayer structure, the surface of the antistatic layer side of the layer containing release resin configured on the antistatic layer side is preferably corona treated or plasma treated.
[0113] (Antistatic layer)
[0114] The antistatic layer is not particularly limited as long as it has an antistatic function. The antistatic layer may be provided on the substrate adjacent to the substrate, or may be provided on the substrate via another layer adjacent to the substrate.
[0115] The antistatic layer may contain an antistatic agent. Examples of the antistatic agent include ionic liquids, conductive polymers, and conductive fillers. The antistatic agent may be used alone or in combination of two or more.
[0116] The ionic liquid may, for example, be an onium compound such as pyridinium or imidazolium, or a fluorine compound.
[0117] The conductive polymer refers to a polymer in which electrons move and diffuse along the polymer skeleton. Examples of the conductive polymer include polyaniline polymers, polyacetylene polymers, polyparaphenylene polymers, polypyrrole polymers, polythiophene polymers, and polyvinylcarbazole polymers.
[0118] The conductive filler may, for example, be a metal ion conductive salt, a metal compound (eg, a metal oxide), a filler coated with a metal compound (eg, a metal oxide), conductive carbon, or conductive carbon nanotube.
[0119] As the metal ion conductive salt, a lithium salt compound or the like may be mentioned.
[0120] Examples of the metal oxide as the filler and the metal oxide coating the filler include tin oxide, tin-doped indium oxide, antimony-doped tin oxide, phosphorus-doped tin oxide, zinc antimonate, and antimony oxide.
[0121] From the viewpoint of excellent heat resistance and conductivity, the antistatic agent is preferably at least one selected from a polyaniline polymer, a polyacetylene polymer, a polyparaphenylene polymer, a polypyrrole polymer, a polythiophene polymer, and a polyvinylcarbazole polymer.
[0122] The antistatic agent is preferably dispersed in the binder resin. That is, the antistatic layer is preferably a layer in which the antistatic agent is dispersed in the binder resin.
[0123] As the binder resin, a heat-resistant binder resin is preferred. For example, when the film is used in a sealing step of a semiconductor element, it is preferred to have heat resistance at about 180°C.
[0124] From the viewpoint of excellent heat resistance, the binder resin preferably contains at least one selected from (meth) acrylic resin, silicone resin, polyurethane resin, polyester resin, polyamide resin, vinyl acetate resin, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, trifluorochloroethylene-vinyl alcohol copolymer and tetrafluoroethylene-vinyl alcohol copolymer. Wherein, from the viewpoint of excellent mechanical strength, it is preferably composed of at least one (such as only (meth) acrylic resin) selected from (meth) acrylic resin, silicone resin, polyurethane resin, polyester resin, polyamide resin, vinyl acetate resin, ethylene-vinyl acetate copolymer, ethylene-vinyl alcohol copolymer, trifluorochloroethylene-vinyl alcohol copolymer and tetrafluoroethylene-vinyl alcohol copolymer. In addition, from the viewpoint of excellent heat resistance and dispersibility of antistatic agent, it is preferably selected from at least one of polyester resin and (meth) acrylic resin.
[0125] In the antistatic layer, the binder resin may be cross-linked. If the binder resin is cross-linked, it has better strength, heat resistance, and solvent resistance than when it is not cross-linked.
[0126] In one embodiment, from the viewpoint of solvent resistance, the antistatic layer preferably comprises a carboxyl-containing (meth) acrylic polymer and a reaction solid of at least one selected from a difunctional or higher aziridine compound (hereinafter also referred to as "polyfunctional aziridine compound") and a difunctional or higher epoxy compound (hereinafter also referred to as "polyfunctional epoxy compound") as a binder resin. In this case, the carboxyl-containing (meth) acrylic polymer reacts with at least one selected from a polyfunctional aziridine compound and a polyfunctional epoxy compound to crosslink and form a reaction solid. The antistatic layer can be a carboxyl-containing (meth) acrylic polymer and a reaction solid of at least one selected from a polyfunctional aziridine compound and a polyfunctional epoxy compound and other components.
[0127] The ratio of the units derived from the (meth)acrylic acid monomer to the entire (meth)acrylic acid polymer is not particularly limited, but is preferably 50% by mass or more, more preferably 60% by mass or more, further preferably 70% by mass or more, and particularly preferably 80% by mass or more.
[0128] The carboxyl group of the carboxyl group-containing (meth)acrylic polymer is a crosslinkable functional group that reacts with an aziridine group in a polyfunctional aziridine compound or an epoxy group in a polyfunctional epoxy compound.
[0129] The acid value of the carboxyl-containing (meth) acrylic polymer is preferably 1 to 80 mgKOH / g, more preferably 1 to 40 mgKOH / g, further preferably 1 to 30 mgKOH / g, and particularly preferably 5 to 30 mgKOH / g. The acid value of the carboxyl-containing (meth) acrylic polymer is an indicator of the ease of forming crosslinks when reacting with a polyfunctional aziridine compound or a polyfunctional epoxy compound. If the acid value is below the above upper limit, the stretchability of the antistatic layer is excellent. If the acid value is above the above lower limit, the adhesion of the antistatic layer is excellent.
[0130] When the antistatic layer uses a plurality of (meth)acrylic polymers, the above range is a preferred range of the acid value of the plurality of (meth)acrylic polymers as a whole.
[0131] The acid value of the (meth)acrylic acid polymer is measured according to the method specified in JIS K0070:1992.
[0132] In the carboxyl group-containing (meth)acrylic polymer, the carboxyl group may be present in the side group, at the main chain terminal, or in both the side chain and the main chain. From the viewpoint of easy adjustment of the carboxyl group content, it is preferred that the carboxyl group be present at least in the side group.
[0133] As the carboxyl group-containing (meth)acrylic polymer having a carboxyl group as a pendant, there may be mentioned a (meth)acrylic polymer having a unit based on a carboxyl group-containing monomer.
[0134] Examples of carboxyl-containing monomers include carboxyl-containing (meth) acrylic acid monomers. Examples of carboxyl-containing (meth) acrylic acid monomers include carboxyl-containing (meth) acrylic acid esters and (meth) acrylic acid. Examples of carboxyl-containing (meth) acrylic acid esters include ω-carboxyl-polycaprolactone mono(meth) acrylate and mono-2-((meth) acryloyloxy) ethyl succinic acid. These monomers may be used alone or in combination of two or more.
[0135] The carboxyl group-containing (meth)acrylic polymer may be composed only of units based on a carboxyl group-containing monomer, or may further have units based on a monomer other than the carboxyl group-containing monomer.
[0136] As a monomer other than a carboxyl group-containing monomer, a (meth)acrylate which does not contain a hydroxyl group and a carboxyl group, a (meth)acrylate containing a hydroxyl group, etc. These monomers may be used individually by 1 type, or may use 2 or more types together.
[0137] Examples of the (meth)acrylates containing no hydroxyl group or carboxyl group include alkyl (meth)acrylates, cyclohexyl (meth)acrylates, phenyl (meth)acrylates, toluene (meth)acrylates, benzyl (meth)acrylates, 2-methoxyethyl (meth)acrylates, 3-methoxybutyl (meth)acrylates, glycidyl (meth)acrylates, 2-aminoethyl (meth)acrylates, 3-(methacryloyloxypropyl)trimethoxysilane, trifluoromethyl methyl (meth)acrylates, and trifluoromethyl methyl (meth)acrylates. 2-perfluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate, perfluoromethyl (meth)acrylate, diperfluoromethyl methyl (meth)acrylate, 2-perfluoromethyl-2-perfluoroethyl methyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate, and 2-perfluorohexadecylethyl (meth)acrylate.
[0138] As the alkyl (meth)acrylate, a compound having an alkyl group with 1 to 12 carbon atoms is preferred, and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate.
[0139] Examples of the hydroxyl group-containing (meth)acrylate include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 1,4-cyclohexanedimethanol monoacrylate and 2-acryloyloxyethyl-2-hydroxyethyl-phthalic acid.
[0140] The mass average molecular weight (hereinafter also referred to as "Mw") of the carboxyl-containing (meth) acrylic polymer is preferably 10,000 to 1,000,000, more preferably 50,000 to 800,000, and further preferably 100,000 to 600,000. If Mw is above the above lower limit, the strength of the antistatic layer is excellent. If Mw is below the above upper limit, the stretchability of the antistatic layer is excellent.
[0141] The Mw of the carboxyl group-containing (meth)acrylic polymer is a polystyrene-equivalent value obtained by measuring by gel permeation chromatography using a calibration curve prepared using a standard polystyrene sample with a known molecular weight.
[0142] The polyfunctional aziridine compound is a compound having two or more aziridine groups in one molecule. From the viewpoint of not making the crosslinking density of the antistatic layer too high and obtaining high stretchability, the number of aziridine groups in the polyfunctional aziridine compound is preferably 6 or less, particularly preferably 3 or less.
[0143] Examples of the polyfunctional aziridine compound include 2,2-dihydroxymethylbutanol-tris[3-(1-aziridinyl)propionate], 4,4-bis(ethyleneiminocarbonylamino)diphenylmethane, and trimethylolpropane-tris(β-aziridinyl)propionate. The polyfunctional aziridine compound may be used alone or in combination of two or more.
[0144] Commercially available products may be used as the polyfunctional aziridine compound, and examples of commercially available products include ARACOAT CL910 (trade name) manufactured by Arakawa Chemical Industries, Ltd., Chemitite (registered trademark) DZ-22E (trade name) manufactured by Nippon Shokubai Co., Ltd., and Chemitite (registered trademark) PZ-33 (trade name) manufactured by Nippon Shokubai Co., Ltd.
[0145] From the viewpoint of not making the crosslinking density of the antistatic layer too high and obtaining high stretchability, the aziridine equivalent of the multifunctional aziridine compound is preferably above 50 g / eq, more preferably above 75 g / eq, and further preferably above 100 g / eq. From the viewpoint of improving the strength of the antistatic layer, the aziridine equivalent of the multifunctional aziridine compound is preferably below 300 g / eq, more preferably below 250 g / eq, and further preferably below 200 g / eq. From this viewpoint, the aziridine equivalent of the multifunctional aziridine compound is preferably 50 to 300 g / eq, more preferably 75 to 250 g / eq, and further preferably 100 to 200 g / eq.
[0146] The polyfunctional epoxy compound is a compound having two or more epoxy groups in one molecule. From the viewpoint of not making the crosslinking density of the antistatic layer too high and obtaining high stretchability, the number of epoxy groups in the polyfunctional epoxy compound is preferably 6 or less, particularly preferably 3 or less.
[0147] Examples of the polyfunctional epoxy compound include N,N,N',N'-tetraglycidyl-m-xylylenediamine, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, resorcinol diglycidyl ether, glycerol polyglycidyl ether, etc. The epoxy compound may be used alone or in combination of two or more.
[0148] The polyfunctional epoxy compound may be a commercially available product, and examples of the commercially available products include TETRAD-X (trade name) and TETRAD-C (trade name) manufactured by Mitsubishi Gas Chemical Co., Ltd., and Denacol (registered trademark) EX-201 (trade name) and Denacol (registered trademark) EX-313 (trade name) manufactured by Nagase ChemteX Co., Ltd.
[0149] From the viewpoint of not making the crosslinking density of the antistatic layer too high and obtaining high stretchability, the epoxy equivalent of the multifunctional epoxy compound is preferably above 30 g / eq, more preferably above 50 g / eq, and further preferably above 90 g / eq. From the viewpoint of improving the strength of the antistatic layer, the epoxy equivalent of the multifunctional epoxy compound is preferably below 300 g / eq, more preferably below 200 g / eq, further preferably below 150 g / eq, and particularly preferably below 120 g / eq. From this viewpoint, the epoxy equivalent of the multifunctional epoxy compound is preferably 30 to 300 g / eq, more preferably 50 to 200 g / eq, and further preferably 90 to 120 g / eq.
[0150] Relative to 100 mol% of the carboxyl of the (meth) acrylic polymer containing carboxyl, the total ratio of the aziridine radicals of the polyfunctional aziridine compound and the epoxy groups of the polyfunctional epoxy compound is preferably 15 to 130 mol%, more preferably 15 to 90 mol%, and particularly preferably 15 to 60 mol%. If the total ratio of aziridine radicals and epoxy groups is below the above-mentioned upper limit, the cross-linking density is low enough, and the adhesion between the release layer and the antistatic layer is excellent. If the total ratio of aziridine radicals and epoxy groups is above the above-mentioned lower limit, the cross-linking density is high enough, and the strength of the antistatic layer is excellent.
[0151] The antistatic layer may contain other components in addition to the antistatic agent and the binder resin. Examples of other components include lubricants, colorants, coupling agents, and the like.
[0152] Examples of the lubricant include microbeads made of thermoplastic resin, fumed silica, and polytetrafluoroethylene (PTFE) fine particles.
[0153] Examples of the colorant include various organic colorants and inorganic colorants, and more specifically, cobalt blue, Bengal red, phthalocyanine blue, and the like.
[0154] As the coupling agent, a silane coupling agent, a titanate coupling agent, etc. may be mentioned.
[0155] From the viewpoint of sufficiently exerting the antistatic function, the content of the antistatic agent in the antistatic layer is preferably an amount such that the surface resistance value of the film falls within the following range.
[0156] In one embodiment, when the antistatic layer is a layer obtained by dispersing an antistatic agent in a binder resin, the content of the antistatic agent relative to the binder resin can be 3 to 50% by mass, or 5 to 20% by mass. If the content of the antistatic agent is above the above lower limit, the surface resistance value of the film is easily within an appropriate range. If the content of the antistatic agent is below the above upper limit, the adhesion of the antistatic layer is easily improved.
[0157] The contents of other components are appropriately set according to the desired surface resistance and strength of the antistatic layer.
[0158] The thickness of the antistatic layer is preferably 0.05 to 3.0 μm, more preferably 0.1 to 2.5 μm. If the thickness of the antistatic layer is above the lower limit, the conductivity is exhibited and the antistatic function is excellent. If the thickness of the antistatic layer is below the upper limit of the above range, the stability of the production process represented by the appearance of the coated surface is excellent.
[0159] (Release layer)
[0160] The release layer may be disposed on the antistatic layer adjacent to the antistatic layer, or may be disposed on the antistatic layer via another layer adjacent to the antistatic layer.
[0161] The material of the release layer is not particularly limited.
[0162] The release layer may be a layer having adhesiveness to other members.
[0163] In one embodiment, from the viewpoint of heat resistance to be able to withstand the use in the transfer molding process where the mold and the sealing resin are at high temperature and compatibility with the antistatic agent, the release layer preferably comprises a reaction solidified product of a hydroxyl-containing (meth) acrylate and a difunctional or higher isocyanate compound (hereinafter also referred to as a "polyfunctional isocyanate compound"). In this case, the hydroxyl-containing (meth) acrylic polymer reacts and crosslinks with the polyfunctional isocyanate compound to form a reaction solidified product. The release layer may also be a reaction solidified product of a hydroxyl-containing (meth) acrylic polymer, a polyfunctional isocyanate compound and other components.
[0164] The hydroxyl group of the hydroxyl-containing (meth)acrylic polymer is a crosslinking functional group that reacts with the isocyanate group in the polyfunctional isocyanate compound.
[0165] The hydroxyl value of the hydroxyl-containing (meth)acrylic polymer is preferably 1 mgKOH / g or more, more preferably 29 mgKOH / g or more, and preferably 100 mgKOH / g or less.
[0166] When a plurality of (meth)acrylic polymers are used in the release layer, the above range is a preferred range of the hydroxyl value of the plurality of (meth)acrylic polymers as a whole.
[0167] The hydroxyl value is measured according to the method specified in JIS K0070:1992.
[0168] The hydroxyl group-containing (meth)acrylic polymer may or may not have a carboxyl group. Like the hydroxyl group, the carboxyl group is a crosslinking functional group that reacts with an isocyanate group in a polyfunctional isocyanate compound.
[0169] The acid value of the hydroxyl group-containing (meth)acrylic polymer is preferably 100 mgKOH / g or less, more preferably 30 mgKOH / g or less, and may be 0 mgKOH / g.
[0170] The crosslinking functional group equivalent of the hydroxyl group-containing (meth)acrylic polymer, that is, the total equivalent of the hydroxyl group and the carboxyl group, is preferably 500 g / mol or more, more preferably 1000 g / mol or more, and preferably 2000 g / mol or less.
[0171] The cross-linking functional group equivalent is equivalent to the molecular weight between cross-linking points, and is a physical property value that determines the elastic modulus after cross-linking, i.e. the elastic modulus of the reaction cured product. If the cross-linking functional group equivalent is above the above lower limit, the elastic modulus of the reaction cured product is relatively low, and the tensile property of the release layer is excellent. If the cross-linking functional group equivalent is below the above upper limit, the elastic modulus of the reaction cured product is high, and the release layer is excellent in the release property of resins, electronic components, etc. In addition, the components of the release layer can be suppressed from migrating to resins, electronic components, etc.
[0172] The crosslinking functional group equivalent of the hydroxyl-containing (meth)acrylic polymer can be determined by dividing the molecular weight of potassium hydroxide (56.1) by the sum of the hydroxyl value and the acid value of the hydroxyl-containing (meth)acrylic polymer and multiplying the result by 1,000.
[0173] In the hydroxyl-containing (meth)acrylic polymer, the hydroxyl group may be present in the side group, at the main chain terminal, or in both the side chain and the main chain. From the viewpoint of easy adjustment of the hydroxyl content, it is preferred that the hydroxyl group be present at least in the side group.
[0174] As the hydroxyl group-containing (meth)acrylic polymer having a hydroxyl group present in a side group, a copolymer having the following units c1 and c2 is preferred.
[0175] Unit c1: a hydroxyl group-containing (meth)acrylate unit.
[0176] Unit c2: a unit other than unit c1.
[0177] As the unit c1, for example, a unit represented by the following formula 1 may be mentioned.
[0178] -(CH2-CR 1 (COO-R 2-OH))-Formula 1
[0179] Among them, R 1 is a hydrogen atom or a methyl group; R 2 is an alkylene group having 2 to 10 carbon atoms, a cycloalkylene group having 3 to 10 carbon atoms, or -R 3 -OCO-R 5 -COO-R 4 -. R 3 and R 4 are each independently an alkylene group having 2 to 10 carbon atoms, R 5 It is a phenylene group.
[0180] As R 1 , preferably a hydrogen atom.
[0181] R 2 , R 3 , R 4 The alkylene group in the group may be linear or branched.
[0182] Specific examples of the monomer forming the unit c1 include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 1,4-cyclohexanedimethanol monoacrylate, and 2-acryloyloxyethyl-2-hydroxyethyl-phthalic acid. The monomer forming the unit c1 may be used alone or in combination of two or more.
[0183] As the unit c1, from the viewpoint of excellent reactivity of the hydroxyl group, R in the above formula 1 is preferably 2 The unit is an alkylene group having 2 to 10 carbon atoms. That is, the unit is preferably a hydroxyalkyl (meth)acrylate having a hydroxyalkyl group having 2 to 10 carbon atoms.
[0184] The ratio of the unit c1 to the total of all units constituting the hydroxyl-containing (meth) acrylic polymer (100 mol%) is preferably 3 mol% or more, and is also preferably 40 mol% or less, more preferably 30 mol% or less, and further preferably 20 mol% or less. If the ratio of the unit c1 is above the lower limit, the crosslinking density based on the polyfunctional isocyanate compound is sufficiently high, and the mold release layer has excellent releasability to resins and electronic components. If the ratio of the unit c1 is below the upper limit, the mold release layer has excellent adhesion.
[0185] Unit c2 is not particularly limited as long as it is copolymerizable with the monomer forming unit c1. Unit c2 may have a carboxyl group, but preferably does not have a reactive group (eg, an amino group) other than a carboxyl group that can react with an isocyanate group.
[0186] The monomer to form the unit c2 may, for example, be a macromolecule containing an unsaturated double bond, a (meth)acrylate having no hydroxyl group, (meth)acrylic acid, or acrylonitrile.
[0187] As the macromolecule containing an unsaturated double bond, a macromolecule having a polyoxyalkylene chain such as (meth)acrylate of polyethylene glycol monoalkyl ether may, for example, be mentioned.
[0188] Examples of the (meth)acrylate not having a hydroxyl group include alkyl (meth)acrylates, cyclohexyl (meth)acrylate, phenyl (meth)acrylate, toluene (meth)acrylate, benzyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxybutyl (meth)acrylate, glycidyl (meth)acrylate, 2-aminoethyl (meth)acrylate, 3-(methacryloxypropyl)trimethoxysilane, trifluoromethylmethyl (meth)acrylate, and (meth)acrylate. )2-trifluoromethylethyl (meth)acrylate, 2-perfluoroethylethyl (meth)acrylate, 2-perfluoroethyl-2-perfluorobutylethyl (meth)acrylate, 2-perfluoroethyl (meth)acrylate, perfluoromethyl (meth)acrylate, diperfluoromethyl methyl (meth)acrylate, 2-perfluoromethyl-2-perfluoroethyl methyl (meth)acrylate, 2-perfluorohexylethyl (meth)acrylate, 2-perfluorodecylethyl (meth)acrylate and 2-perfluorohexadecylethyl (meth)acrylate, etc.
[0189] As the alkyl (meth)acrylate, a compound having an alkyl group with 1 to 12 carbon atoms is preferred, and examples thereof include methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and dodecyl (meth)acrylate.
[0190] The unit c2 preferably contains at least a unit based on an alkyl (meth)acrylate.
[0191] The ratio of the (meth)acrylic acid alkyl ester unit to the total of all units constituting the hydroxyl-containing (meth)acrylic acid polymer (100 mol%) is preferably 60 mol% or more, more preferably 70 mol% or more, further preferably 80 mol% or more, and preferably 97 mol% or less. If the ratio of the (meth)acrylic acid alkyl ester unit is above the above lower limit, the glass transition temperature, mechanical properties, etc. derived from the structure of the (meth)acrylic acid alkyl ester are present, and the mechanical strength and adhesion of the release layer are excellent. If the ratio of the (meth)acrylic acid alkyl ester unit is below the above upper limit, the content of the hydroxyl group is sufficient, so the crosslinking density increases and a high elastic modulus can be presented.
[0192] The Mw of the hydroxyl-containing (meth)acrylic polymer is preferably 100,000 to 1,200,000, more preferably 200,000 to 1,000,000, and further preferably 200,000 to 700,000. If the Mw is above the lower limit, the mold release layer has excellent releasability to resins, electronic components, etc. If the Mw is below the upper limit, the mold release layer has excellent adhesion.
[0193] The Mw of the hydroxyl-containing (meth)acrylic polymer is a polystyrene-equivalent value obtained by measuring by gel permeation chromatography using a calibration curve prepared using a standard polystyrene sample with a known molecular weight and using the calibration curve.
[0194] The glass transition temperature (Tg) of the hydroxyl-containing (meth)acrylic polymer is preferably 20° C. or lower, more preferably 0° C. or lower. When Tg is at most the upper limit value above, the release layer exhibits sufficient flexibility even at low temperatures and is not easily peeled from the substrate.
[0195] The lower limit of Tg is not particularly limited, but is preferably -60°C or higher within the above-mentioned molecular weight range.
[0196] Tg is the midpoint glass transition temperature measured by differential scanning calorimetry (DSC).
[0197] The polyfunctional isocyanate compound is a compound having two or more isocyanate groups in one molecule. The isocyanate group may be protected with a blocking agent.
[0198] From the viewpoint of preventing the crosslinking density of the release layer from being too high and obtaining high stretchability, the number of isocyanate groups in the polyfunctional isocyanate compound is preferably 10 or less, particularly preferably 3 or less. The polyfunctional isocyanate compound is most preferably difunctional or trifunctional.
[0199] As the polyfunctional isocyanate compound, for example, hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), naphthalene diisocyanate (NDI), dimethylbiphenyl diisocyanate (TODI), isophorone diisocyanate (IPDI), xylylene diisocyanate (XDI), triphenylmethane triisocyanate and thiophosphoric acid triphenyl isocyanate. In addition, isocyanurate bodies (i.e., trimers) and biuret bodies of these polyfunctional isocyanate compounds, and reactants of these polyfunctional isocyanate compounds with polyol compounds (e.g., adducts, difunctional prepolymers, and trifunctional prepolymers, etc.). In addition, compounds in which the isocyanate groups of these polyfunctional isocyanate compounds are protected by blocking agents can also be exemplified. As blocking agents, phenols such as meta-cresol and guaiacol, benzenethiol, ethyl acetoacetate, diethyl malonate, ε-caprolactam, etc. can be exemplified.
[0200] Difunctional prepolymers such as OCN-R 6 -NHC(=O)OR 7 -OC(=O)NH-R 6 -NCO means. 6 It is a residue obtained by removing two isocyanate groups from a diisocyanate compound. 7 It is a residue obtained by removing two hydroxyl groups from a diol compound. As diisocyanate compounds, HDI, TDI, MDI, NDI, TODI, IPDI and XDI can be cited, and HDI and IPDI are preferred from the viewpoint of yellowing resistance. As diol compounds, ethylene glycol, propylene glycol and the like can be cited. Commercially available products can be used for difunctional prepolymers. As examples of commercially available products, Duranate (registered trademark) D201 (trade name) and D101 manufactured by Asahi Kasei Corporation can be cited.
[0201] Examples of the trifunctional prepolymer include isocyanurate forms of HDI (isocyanurate-type HDI), isocyanurate forms of TDI (isocyanurate-type TDI), isocyanurate forms of MDI (isocyanurate-type MDI), and reaction products of trifunctional polyols and difunctional isocyanates, etc. From the viewpoint of yellowing resistance, isocyanurate-type HDI is preferred.
[0202] In one embodiment, the polyfunctional isocyanate compound preferably has an isocyanurate ring, which is preferred from the viewpoint that the reaction cured product (ie, release layer) exhibits a high elastic modulus due to the planarity of the ring structure.
[0203] As the polyfunctional isocyanate compound having an isocyanurate ring, isocyanurate type HDI, isocyanurate type TDI, isocyanurate type MDI, etc. may be mentioned.
[0204] The ratio of the isocyanate group of the polyfunctional isocyanate compound to 100 mol% of the hydroxyl group of the (meth) acrylic polymer containing hydroxyl group is preferably 20 to 115 mol%, more preferably 20 to 80 mol%, and particularly preferably 20 to 70 mol%. If the ratio of the isocyanate group is below the above upper limit, the crosslinking density is sufficiently low, and the adhesion between the release layer and the antistatic layer is excellent. If the ratio of the isocyanate group is above the above lower limit, the crosslinking density is sufficiently high, and the release layer is excellent in the releasability of the resin and electronic components.
[0205] In the release layer, the content of the reaction cured product of the hydroxyl-containing (meth)acrylic polymer and the polyfunctional isocyanate compound is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more based on the total mass of the release layer.
[0206] The release layer may contain other components in addition to the above-mentioned reaction cured product. Examples of other components include crosslinking catalysts (such as amines, metal compounds, and acids), reinforcing fillers, coloring dyes, pigments, and antistatic agents.
[0207] The crosslinking catalyst may be any substance that catalyzes the reaction (urethanization reaction) of the hydroxyl-containing (meth) acrylic copolymer and the polyfunctional isocyanate compound, and a general urethanization reaction catalyst may be used. Examples of the crosslinking catalyst include amine compounds such as tertiary amines, organic metal compounds such as organic tin compounds, organic lead compounds, and organic zinc compounds. Examples of tertiary amines include trialkylamines, N,N,N',N'-tetraalkyldiamines, N,N-dialkylaminoalcohols, triethylenediamine, morpholine derivatives, and piperazine derivatives. Examples of the organic tin compound include dialkyltin oxides, fatty acid salts of dialkyltins, and fatty acid salts of stannous (Japanese: first tin).
[0208] As the crosslinking catalyst, an organic tin compound is preferred, and dioctyltin oxide, dioctyltin dilaurate, dibutyltin laurate, and dibutyltin dilaurate are more preferred. In addition, a dialkyltin acetylacetonate tin complex catalyst having a structure in which one atom of dialkyltin and two molecules of acetylacetone are coordinated and synthesized by reacting a dialkyltin ester with acetylacetone in a solvent may also be used.
[0209] The amount of the crosslinking catalyst used is preferably 0.01 to 0.5 parts by mass based on 100 parts by mass of the hydroxyl-containing (meth)acrylic polymer.
[0210] The thickness of the release layer is preferably 0.05 to 3.0 μm, more preferably 0.05 to 2.5 μm, and further preferably 0.05 to 2.0 μm. If the thickness of the adhesive layer is above the lower limit, the release property is excellent. If the thickness of the release layer is below the upper limit, the function of the antistatic layer is fully manifested, and the surface resistance value of the release layer side of the film becomes low.
[0211] (Other layers)
[0212] The film may or may not have other layers other than the substrate, antistatic layer and release layer. Other layers may include a gas barrier layer, a coloring layer, etc. These layers may be used alone or in combination of two or more.
[0213] (Method for producing film)
[0214] The present film is produced, for example, by the following method.
[0215] The antistatic layer coating liquid comprising the antistatic layer composition and the liquid medium is coated on a surface of the substrate and dried to form an antistatic layer. On the surface of the antistatic layer formed on the opposite side of the substrate, the release layer coating liquid comprising the release layer composition and the liquid medium is coated and dried to form a release layer. Other arbitrary layers can also be formed. In the formation of each layer, heating can be performed in order to promote solidification. Heating can be performed when each layer is formed, or after forming multiple layers.
[0216] The antistatic layer composition preferably contains an antistatic agent, a carboxyl group-containing (meth)acrylic polymer, and at least one selected from a polyfunctional aziridine compound and a polyfunctional epoxy compound. In addition, the antistatic layer composition does not contain a liquid medium.
[0217] The release layer composition preferably contains a hydroxyl group-containing (meth)acrylic polymer and a polyfunctional isocyanate compound. In addition, the release layer composition does not contain a liquid medium.
[0218] (Surface resistance of the film)
[0219] The surface resistance value of the present film is not particularly limited and can be 10 17 Ω / □ or less, preferably 10 11 Ω / □ or less, more preferably 10 10 Ω / □ or less, more preferably 10 9 The lower limit of the surface resistance value is not particularly limited.
[0220] The surface resistance value of the present film is measured in accordance with IEC 60093:1980: double ring electrode method under the conditions of an applied voltage of 500 V and an applied time of 1 minute. As a measuring instrument, for example, an ultra high resistance meter R8340 (Advantec Corporation) can be used.
[0221] (Use of membrane)
[0222] This film can be used, for example, as a release film used in the process of sealing a semiconductor element with a curable resin and as a surface protection film for semiconductor elements, solar cell modules, etc. Among them, it can be used as a release film used in the process of producing a semiconductor package having a complex shape, such as a sealed body in which a part of an electronic component is exposed from the resin.
[0223] [Method for manufacturing semiconductor package]
[0224] In one embodiment, a method for manufacturing a semiconductor package includes: configuring the present film on the inner surface of a mold; configuring a substrate having a semiconductor element fixed thereon in the mold configured with the present film; sealing the semiconductor element in the mold with a curable resin to produce a sealed body; and demolding the sealed body from the mold.
[0225] Examples of semiconductor packages include integrated circuits in which semiconductor elements such as transistors and diodes are integrated, and light-emitting diodes having light-emitting elements.
[0226] The package shape of the integrated circuit may be a shape that covers the entire integrated circuit or a shape that covers a part of the integrated circuit (that is, a shape that exposes a part of the integrated circuit). Specific examples include SIP (Single In-line Package), ZIP (Zigzag In-line Package), DIP (Dual In-line Package), SOJ (Small Outline J-leaded package), SON (Small Outline Non-leaded package), SOI (Small Outline I-leaded package), SOF (Small Outline F-leaded package), QFP (Quad Flat Package), QFJ (Quad Flat J-leaded package), QFN (Quad Flat Non-leaded package), QFF (Quad Flat F-leaded package), PGA (Pin Grid Array), LGA (Land Grid Array), and so on. Array: Planar Grid Array), BGA (Ball Grid Array), DTP (Dual Tape Carrier Package), QTP (Quad Tape Carrier Package), CSP (Chip Size Package / Chip Scale Package), WL-CSP (Wafer Lebel CSP), LLP (Leadless Lead Frame Package), DFN (Dual Flatpack No-leaded), MCP (Multi Chip Package), MCM (Multi Chip Module), SiP (System in a Package), PoP (Package on a Package), PiP (Package in a Package),Package: stacked package), QIP (or QUIP) (Quad In-line Package: quad in-line package), CFP (Ceramic Flat Package: ceramic flat package), LLCC (Lead Less Chip Carrier: leadless chip carrier), FOWLP (Fan Out Wafer Level Package: fan-out wafer level package), COB (Chip On Board: chip on board), COF (Chip On Film: chip on film), COG (Chip On Glass: chip on glass) and SVP (Surface Vertical Package: surface vertical package), etc.
[0227] As a semiconductor package, from the perspective of productivity, a package manufactured through batch packaging (Japanese: one-piece packaging) and single-chip packaging (Japanese: シンギュレーション) is preferred, and examples include integrated circuits whose sealing method is MAP (Moldied Array Packaging) or WL (Wafer Level Packaging).
[0228] As the curable resin, thermosetting resins such as epoxy resins and silicone resins are preferred, and epoxy resins are more preferred.
[0229] In one embodiment, the semiconductor package may or may not have electronic components such as a source electrode and a sealing glass in addition to the semiconductor element. In addition, a part of the semiconductor element, the source electrode, and the electronic components such as the sealing glass may be exposed from the resin.
[0230] In the method for manufacturing the semiconductor package, in addition to using the present film, a known manufacturing method can be used. For example, as a method for sealing a semiconductor element, a transfer molding method can be cited, and as an apparatus used at this time, a known transfer molding apparatus can be used. The manufacturing conditions can also be the same as those of the known method for manufacturing a semiconductor package.
[0231] Example
[0232] The embodiments of the present disclosure are described in detail below by way of examples, but the embodiments of the present disclosure are not limited to these examples. In the following examples, Examples 2 to 4, 7, 8, 10 to 13, 16, 17 and 19 are examples, and Examples 1, 5, 6, 9, 14, 15 and 18 are comparative examples. "Parts" means "parts by mass".
[0233] (Evaluation method)
[0234] <Elongation>
[0235] Cut the film into strips (50 mm wide and 100 mm long). Clamp the film and fix it in the clamp of a tensile testing machine (e.g., RTC-131-A manufactured by Nippon Kaisha Instruments Co., Ltd.). Stretch the film at a speed of 100 mm / min with a distance of 10 mm between the clamps before stretching until the film breaks, and measure the elongation (mm) at break. The measurement is carried out at 23°C. The elongation is calculated by the following formula. The results are shown in Table 1.
[0236] Elongation (%) = elongation at break (mm) / distance between clamps before stretching (10mm) × 100
[0237] <Surface resistance value>
[0238] The surface resistance (Ω / □) of the release layer side of the film was measured according to IEC 60093:1980: double ring electrode method. Ultra high resistance meter R8340 (Advantec Corporation) was used as a measuring instrument, and the measurement was performed under the conditions of applying voltage of 500 V and application time of 1 minute.
[0239] <Preparation of epoxy resin composition for mold release test>
[0240] The following materials were pulverized and mixed for 5 minutes using a super mixer to prepare an epoxy resin composition for a sealing test.
[0241] 8 parts of phenylene skeleton-containing phenol aralkyl type epoxy resin (softening point 58°C, epoxy equivalent 277),
[0242] 2 parts of bisphenol A epoxy resin (melting point 45°C, epoxy equivalent 172),
[0243] 2 parts of phenylene skeleton-containing phenol aralkyl resin (softening point 65°C, hydroxyl equivalent 165),
[0244] 2 parts of phenol novolac resin (softening point 80°C, hydroxyl equivalent 105),
[0245] Curing accelerator (triphenylphosphine) 0.2 parts,
[0246] Inorganic filler (fused spherical silica with a median diameter of 16 μm) 84 parts,
[0247] 0.1 parts of carnauba wax,
[0248] 0.3 parts of carbon black,
[0249] Coupling agent (3-glycidoxypropyltrimethoxysilane) 0.2 parts.
[0250] The cured product of the epoxy resin composition had a glass transition temperature of 135° C., a storage modulus of 6 GPa at 130° C., and a storage modulus of 1 GPa at 180° C.
[0251] <Mold release test>
[0252] The film of each example was used as a release film, the epoxy resin composition for release test was used as a curable resin, and a sealing device (transfer molding device G-LINE manual system, Yamada Advanced Technology Co., Ltd.) was used to perform a release test in the following order. A semiconductor element was fixed to a copper lead frame of 70 mm × 230 mm.
[0253] Five 5mm×5mm protrusions are evenly spaced on the upper mold of a mold having an upper mold and a lower mold, and a film roll with a width of 190mm is set in a roll-to-roll manner. The film is arranged in a manner that the substrate is located on the side with the five protrusions. After the lead frame with the semiconductor element fixed is arranged in the lower mold, the film is vacuum adsorbed on the upper mold, the mold is closed, and the curing resin is injected after the mold is closed. At this time, in order to expose a part of the semiconductor element from the resin, the surface of the release layer side of the film is directly contacted with the semiconductor element arranged in the lower mold at the five protrusions of the upper mold, and the sealing resin is filled around it. After pressurization for 5 minutes, the mold is opened and the sealed body is taken out.
[0254] After the mold release test, the appearances of the release layer of the release film and the release surface of the cured product of the curable resin were visually checked and evaluated based on the following criteria.
[0255] A: The release layer is not attached to the surface of the cured product of the curable resin, and the release layer is not peeled off or damaged.
[0256] B-1: The release layer adhered to the surface of the cured product of the curable resin and no residue of the release layer existed on the release layer side. It is believed that both the antistatic layer and the release layer were over-cured, so the interlayer adhesion was poor and peeling occurred at the interface.
[0257] B-2: A release layer is attached to the surface of the cured product of the curable resin, and no residue of the release layer exists on the release layer side. It is believed that the difference in shrinkage rate caused by the amount of curing agent reactive groups in the antistatic layer and the release layer relative to the main agent is large or small, resulting in peeling at the interface.
[0258] C: A release layer is attached to the surface of the cured product of the curable resin and there is a residue of the release layer on the release film side. It is believed that the amount of curing agent reactive groups relative to the main agent in both the antistatic layer and the release layer is extremely small, so although the interlayer adhesion is good and interface peeling does not occur, the release property is not exhibited and cohesive failure occurs in the release layer.
[0259] (Materials used)
[0260] <Base Material>
[0261] ETFE film: Fluon (registered trademark) ETFE C-88AXP (AGC Co., Ltd.) was supplied to an extruder equipped with a T-die, and pulled out from between a pressing roller and a mirror metal roller having an uneven surface to produce a 100 μm thick film. The temperature of the extruder and the T-die was 320°C, and the temperature of the pressing roller and the metal roller was 100°C. The surface Ra of the obtained film was 2.0 μm on the pressing roller side and 0.2 μm on the mirror side. Corona treatment was applied to the mirror side to make the wet tension based on ISO 8296:1987 (JIS K6768:1999) above 40 mN / m. The obtained film was wound up to form a roll.
[0262] <Material for antistatic layer>
[0263] Main agent 1: ARACOAT (registered trademark) AS601D (produced by Arakawa Chemical Industries, Ltd.), solid content 3.4% by mass, conductive polythiophene 0.4% by mass, carboxyl group-containing (meth)acrylic polymer 3.0% by mass.
[0264] Curing agent 1-1: ARACOAT CL910 (manufactured by Arakawa Chemical Industries, Ltd.), solid content 10 mass %, trifunctional aziridine compound (2,2-dimethylolbutanol-tris[3-(1-aziridinyl)propionate]), aziridine equivalent 142 g / eq.
[0265] Curing agent 1-2: Chemitite (registered trademark) DZ-22E (manufactured by Nippon Shokubai Co., Ltd.), solid content: 25 mass %, difunctional aziridine compound (4,4-bis(ethyleneiminocarbonylamino)diphenylmethane), aziridine equivalent: 165 g / eq.
[0266] <Material of release layer>
[0267] Main agent 2: Nissetsu (registered trademark) KP2562 (manufactured by Nippon Carbide Industries, Ltd.), solid content 35% by mass, hydroxyl-containing (meth)acrylic polymer (hydroxyl value 70 mgKOH / g, crosslinking functional group equivalent 801 g / mol).
[0268] Curing agent 2-1: Nissetsu CK157 (manufactured by Nippon Carbide Industries, Ltd.), solid content: 100 mass %, trifunctional isocyanate compound (isocyanurate-type hexamethylene diisocyanate), NCO content: 21 mass %.
[0269] Curing agent 2-2: Duranate (registered trademark) D201 (manufactured by Asahi Kasei Corporation), solid content 100% by mass, difunctional isocyanate compound (difunctional prepolymer type hexamethylene diisocyanate: OCN-R-NHC(=O)O-R'-OC(=O)NH-R-NCO), NCO content 15.8% by mass.
[0270] (Example 1)
[0271] An antistatic layer coating liquid was prepared by mixing 10 parts of the main agent 1, 1 part of the curing agent 1-1 and methanol. The amount of methanol added was such that the solid content of the antistatic layer coating liquid was 2% by mass.
[0272] The antistatic coating liquid obtained was applied to the surface of the corona treated side of the substrate by a gravure coater and dried to form an antistatic layer with a thickness of 0.8 μm. A roller with a grid of 150# and a depth of 40 μm and a width of Φ100 mm×250 mm was used as a gravure plate, and the coating was performed by direct gravure method. The coating was passed through a roller-supported drying furnace at 55°C for 1 minute and dried at an air volume of 19 m / s.
[0273] Next, 100 parts of the main agent 2, 6 parts of the curing agent 2-1 and ethyl acetate were mixed to prepare a release layer coating liquid. The amount of ethyl acetate blended was such that the solid content of the release layer coating liquid was 25% by mass.
[0274] The release layer coating liquid obtained was applied to the surface of the substrate on which the antistatic layer was formed by a gravure coater and dried to form a release layer with a thickness of 0.8 μm. A roller with a grid of 150# and a depth of 40 μm and a width of Φ100 mm×250 mm was used as a gravure, and the coating was performed by direct gravure. The film was dried at 100°C for 1 minute in a roller-supported drying furnace with an air volume of 19 m / s. The film was then cured at 40°C for 120 hours to obtain a film.
[0275] (Examples 2~19)
[0276] A film was produced in the same manner as in Example 1 except that the amount of the main agent and the type and amount of the curing agent blended in the antistatic layer coating liquid and the release layer coating liquid were changed to those shown in Tables 1 and 2.
[0277] Tables 1 and 2 show the elongation, surface resistance value, and mold release test results of the obtained films.
[0278] In Tables 1 and 2, "aziridine groups relative to 100 mol% of COOH" is the ratio of aziridine groups of the aziridine compound to 100 mol% of carboxyl groups of the carboxyl group-containing (meth)acrylic polymer. "NCO relative to 100 mol% of OH" is the ratio of isocyanate groups of the isocyanate compound to 100 mol% of hydroxyl groups of the hydroxyl group-containing (meth)acrylic polymer. The surface resistance value of "10^8" means 10 8 .
[0279] [Table 1]
[0280]
[0281] [Table 2]
[0282]
[0283] As shown in Tables 1 and 2, the results of the mold release test of the films of Examples 2 to 4, 7, 8, 10 to 13, 16, 17 and 19, which had an elongation of more than 90% and less than 255%, were all A.
[0284] Possibility of industrial application
[0285] When the film disclosed herein is used to seal a semiconductor element with a curable resin, the release layer and the antistatic layer are not easily peeled off. The film disclosed herein can be used as a release film to manufacture semiconductor packages such as integrated circuits that integrate semiconductor elements such as transistors and diodes, source electrodes, and electronic components such as sealing glass. The film disclosed herein can also be used as a protective film when processing, transporting, and storing semiconductor elements and solar cell modules.
[0286] Explanation of symbols
[0287] 1 film
[0288] 2. Substrate
[0289] 3 Antistatic layer
[0290] 4 Release layer.
Claims
1. A film comprising a substrate, an antistatic layer provided on one surface of the substrate, and a release layer provided on a surface of the antistatic layer opposite to the substrate, wherein: The film has an elongation greater than 90% and less than 255% as measured by a tensile test at 25° C. and a speed of 100 mm / min using the following formula: Elongation (%) = (elongation at break (mm)) × 100 / (distance between the clamps before stretching (mm)).
2. The film according to claim 1, wherein The substrate comprises at least one selected from fluororesin, polymethylpentene, syndiotactic polystyrene, polycyclic olefin, silicone rubber, polyester elastomer, polybutylene terephthalate, polyethylene terephthalate and polyamide.
3. The film according to claim 2, wherein The fluororesin includes at least one selected from the group consisting of ethylene-tetrafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, tetrafluoroethylene-perfluoro(alkyl vinyl ether) copolymer, and tetrafluoroethylene-hexafluoropropylene-vinylidene fluoride copolymer.
4. The film according to any one of claims 1 to 3, wherein The release layer includes a reaction-cured product of a hydroxyl-containing (meth)acrylic polymer and a bifunctional or higher-functional isocyanate compound.
5. The film according to claim 4, wherein The ratio of the isocyanate group of the isocyanate compound is 20 to 115 mol % with respect to 100 mol % of the hydroxyl group of the hydroxyl group-containing (meth)acrylic polymer.
6. The film according to any one of claims 1 to 3, wherein The antistatic layer includes a reaction-cured product of a carboxyl group-containing (meth)acrylic polymer and at least one selected from a difunctional or higher-functional aziridine compound and a difunctional or higher-functional epoxy compound.
7. The film according to claim 6, wherein The total ratio of the aziridine group of the aziridine compound and the epoxy group of the epoxy compound is 15 to 130 mol % with respect to 100 mol % of the carboxyl group of the carboxyl group-containing (meth)acrylic polymer.
8. The film according to any one of claims 1 to 3, wherein The thickness of the substrate is 25-250 μm.
9. The film according to any one of claims 1 to 3, wherein The thickness of the demoulding layer is 0.05 to 3 μm.
10. The film according to any one of claims 1 to 3, wherein The film is a release film used in the step of sealing a semiconductor element with a curable resin.
11. A method for manufacturing a semiconductor package, comprising: Disposing the film according to any one of claims 1 to 3 on the inner surface of the mold; placing a substrate having a semiconductor element fixed thereto in the mold having the film arranged thereon; Sealing the semiconductor element in the mold with a curable resin to produce a sealed body; and The sealing body is demolded from the mold.
Citation Information
Patent Citations
Solid-state battery
JP2022139307A
Film, method for producing same, and method for producing semiconductor element using film
WO2016125796A1